Experimental study into compression after impact strength of laminates with conventional and nonconventional ply orientations. (1st October 2017) - Liv, Yi; Guillamet, G.; Costa, J.; González, E.V.; Marín, L.; Mayugo, J.A.
Abstract: The quest for impact damage tolerant laminates by tailoring stacking sequences has led to nonconventional laminates whose ply sequences are not limited to 0, ±45 and 90°. Departing from the hypothesis that compression after impact (CAI) strength is impaired by the presence of delaminations, a ply sequence was defined by selecting the mismatch angles between plies so as to maintain a central sublaminate with no, or small, delaminations. An experimental test campaign was devoted to validate this hypothesis. To that purpose, baseline and blocked-ply laminates were included in the study. Specimens were tested under low velocity impact followed by compression according to ASTM standards. Delaminations were identified with Ultrasonic C-Scan. The results show delamination locations being successfully predetermined by controlling the mismatch angle, as well as the ensuing improvement in compressive strength retention after impact.